DIGITAL HUMANITIES AND DIGITAL HISTORY (American Journal of Interdisciplinary Research and Development, 2023)
The article analyzes the role of digital technologies in the life of today's society, the emergence of Digital Humanities as a result of the development of these technologies and its essence, the formation of new digital sciences in this field, in particular, the science of Digital History and preliminary research on this science, and the scope of its activities.